Sesquiterpenoids and sesquiterpenoid dimers from the stem bark of Dysoxylum parasiticum (osbeck) kosterm. (January 2023) - Naini, Al Arofatus; Mayanti, Tri; Harneti, Desi; Darwati,; Nurlelasari,; Maharani, Rani; Farabi, Kindi; Herlina, Tati; Supratman, Unang; Fajriah, Sofa; Kuncoro, Hadi; Azmi, Mohamad Nurul; et al.
Abstract: Two undescribed sesquiterpenoids, namely dysoticans A and B, and three undescribed sesquiterpenoid dimers, namely dysoticans C-E, together with six analogs, were isolated from the stem bark of Dysoxylum parasiticum (Osbeck) Kosterm. (Meliaceae), growing in West Java, Indonesia. Their structures were elucidated based on extensive spectroscopic analysis and theoretical simulations of ECD spectra and 13 C NMR shifts. Dysoticans A and B possessed undescribed cadinanes with minor modifications, while C and D featured unprecedented pseudo-sesquiterpenoid dimers through O -ether linkages of cadinanes and guaianes, respectively. Dysotican E was also characterized as the true-sesquiterpenoid dimer featuring eudesmane-germacrene hybrid framework from the Meliaceae family. Furthermore, A-C and E showed moderate activities against the human breast cancer MCF-7 and cervical cancer HeLa cell lines with IC50 values ranging from 22.15 to 45.14 μM. D selectively exhibited significant cytotoxicity against the HeLa cell line with an IC50 value of 13.00 ± 0.13 μM. Graphical abstract: Image 1 Highlights: Eleven sesquiterpenoids were isolated from the stem bark of Dysoxylum parasiticum. Two undescribed cadinanes and three undescribed sesquiterpenoid dimers were found. The absolute configurations were elucidated by ECD technique. Dysoticans A-C and E showed moderate activities against MCF-7 and HeLa cell lines. Dysotican D exhibited selective inhibition against HeLa cell line.